Biochemical alterations in duckweed and algae induced by carrier solvents: Selection of an appropriate solvent in toxicity testing. (26th June 2017) - Hu, Li‐Xin; Tian, Fei; Martin, Francis L.; Ying, Guang‐Guo
Abstract: Carrier solvents are often used in aquatic toxicity testing for test chemicals with hydrophobic properties. However, the knowledge of solvent effects on test organisms remains limited. The present study aimed to determine the biochemical effects of the 4 common solvents methanol, ethanol, acetone, and dimethyl sulfoxide (DMSO) on 2 test species, Lemna minor and Raphidocelis subcapitata, by applying Fourier transform infrared spectroscopy (FTIR) coupled with multivariate analysis to select appropriate solvents for toxicity testing. The results showed biochemical variations associated with solvent treatments at different doses on test species. From the infrared spectra obtained, the structures of lipid membrane and protein phosphorylation in the test species were found to be sensitive to the solvents. Methanol and ethanol mainly affected the protein secondary structure, whereas acetone and DMSO primarily induced alterations in carbohydrates and proteins in the test species. The FTIR results demonstrated that methanol and ethanol showed higher biochemical alterations in the test species than acetone and DMSO, especially at the high doses (0.1 and 1% v/v). Based on the growth inhibition displayed and FTIR spectroscopy, acetone, and DMSO can be used as carrier solvents in toxicity testing when their doses are lower than 0.1% v/v. Environ Toxicol Chem 2017;36:2631–2639. © 2017 SETAC